Elementos da construção da identidade na agricultura familiar no município de Nova Santa Rosa/PR - Thiel, Adriano Marcelo (2017)
The family agriculture, nowadays, is a subject that has linked to several researches in the rural environment, which highlights the importance of the subject. Starting from this emphasis on the subject, the current work intends to analyze how the construction of the identity happens on these individuals, as well as their social interactions in the municipality of Nova Santa Rosa, in the west of Paraná. Since the paper has three initial themes of interest, each of the three chapters deal with one of these subjects. In the first one, an investigation is made of what has already been produced academically about family agriculture, with its different aspects and authors, and especially, how the Brazilian legislation deals with the subject. In the second, an analysis is made of the information of the municipality surveyed, and its relation with the region where it is located, since the identity is also a result of the environment where it is inserted. The third chapter brings information and reflections about identity and how it’s possible to investigate it, as well as the empirical research carried out in this work. Still in the third chapter, it has presented the culmination of the research, because it expresses itself how the subject of family agriculture constitutes its identity and what its references are for this. In the end, it is shown that the subject produces its identity from not only specific elements of family agriculture in the intra-family context, but also by religious, community, historical, economic and many other bonds. Nonetheless, agricultural work is an important reference point of identity, which brings within it elements of other influences that the members of the family agricultural production unit have received, and the way in which these individuals deal with many agricultural issues is associated with identity issues which are beyond the environment exclusively from the current rural labor. A particular attention is also given to the sustainability aspects presented by the respondents, showing how it may be possible to promote sustainability in rural areas, especially in family production units.